Wage subsidies, work incentives, and the reform of the Austrian welfare system - Viktor Steiner; Florian Wakolbinger (Institute for the Study of Labor (IZA), 2010)
We analyze the labor supply and income effects of a needs-based minimum benefit system (Bedarfsorientierte Mindestsicherung) to be introduced in Austria by the end of this/beginning of next year. The aim of this reform is to reduce poverty as well as increasing employment rates of recipients of social assistance. On the basis of a behavioral microsimulation model we show that this new system will slightly increase incomes for the poorest households and slightly reduce labor supply due to the generous allowances for marginal employment under the current and the planned regulations of unemployment assistance. As an alternative, we analyze a reform proposal which reduces financial incentives for marginal employment not covered by social security, and rewards working longer hours by a wage subsidy. Although this alternative reform would yield modest positive labor supply effects, a relatively large number of households would suffer income losses.
Keywords: H31; I38; J22; 330; work incentives; labor supply; social safety system; microsimulation; Sozialreform; Soziale Mindestsicherung; Lohnsubvention; Wirkungsanalyse; Arbeitsangebot; Ökonomischer Anreiz; Niedrigeinkommen; Mikrosimulation; Österreich